'It is an entrustment': Broad consent for genomic research and biobanks in sub‐Saharan Africa. Issue 1 (23rd October 2017) - Tindana, Paulina; Molyneux, Sassy; Bull, Susan; Parker, Michael
Abstract: In recent years, there has been an increase in the establishment of biobanks for genetic and genomic studies around the globe. One example of this is the Human Heredity and Health in Africa Initiative (H3Africa), which has established biobanks in the sub‐region to facilitate future indigenous genomic studies. The concept of 'broad consent' has been proposed as a mechanism to enable potential research participants in biobanks to give permission for their samples to be used in future research studies. However, questions remain about the acceptability of this model of consent. Drawing on findings from empirical research about the role of trust in decision‐making, we argue that an account of entrustment may be an appropriate way of addressing current challenges of seeking consent for biobank research in Africa. We propose a set of key points to consider that can support the proposed entrustment framework.